Radio detections during two state transitions of the intermediate-mass black hole HLX-1. - Webb, N; Cseh, D; Lenc, E; Godet, O; Barret, D; Corbel, S; Farrell, S; Fender, R; Gehrels, N; Heywood, I (2012)
Relativistic jets are streams of plasma moving at appreciable fractions of the speed of light. They have been observed from stellar-mass black holes (~3 to 20 solar masses, M(⊙)) as well as supermassive black holes (~10(6) to 10(9) M(⊙)) found in the centers of most galaxies. Jets should also be produced by intermediate-mass black holes (~10(2) to 10(5) M(⊙)), although evidence for this third class of black hole has, until recently, been weak. We report the detection of transient radio emission at the location of the intermediate-mass black hole candidate ESO 243-49 HLX-1, which is consistent with a discrete jet ejection event. These observations also allow us to refine the mass estimate of the black hole to be between ~9 × 10(3) M(⊙) and ~9 × 10(4) M(⊙).